Autologous fat grafting for cosmetic temporal augmentation: a systematic review - Nasim, Sahra; Nasim, Henna; Kauke, Martin; Safi, Ali-Farid (Frontiers in Surgery, 2024)
BackgroundAutologous fat grafting for temporal augmentation is increasingly popular in aesthetic surgery. However, its high absorption rate, unpredictable volume retention rate, and potential safety risks are significant drawbacks. Evaluation methods for the fat graft survival rate, especially volume retention in the temporal area, vary widely and tend to be more subjective than objective. Therefore, this systematic review aims to analyze the unpredictable volume retention rate, associated safety concerns, and the various assessment strategies following autologous fat grafting for cosmetic temporal augmentation.MethodsWe conducted a systematic review of manuscripts listed in the MEDLINE/PubMed database on autologous fat grafting for cosmetic temporal augmentation. Articles had to be available in full text and written in English. Studies not presenting human data or not discussing cosmetic indications were excluded. We adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.ResultsEight articles were included. The average fat volume injected into each temporal region was 10.69 ml (range 6–17.5) on the right and 10.64 ml (range 5.9–17.4) on the left side. All included articles utilized photographic documentation before and after treatment, along with various questionnaires and scales (37.5% Likert Scale, 12.5% Hollowness Severity Rating Scale, 12.5% Visual Analogue Scale, 12.5% Allergan Temple Hollowing Scale). For objective assessment, one article (12.5%) used computed tomography, and another (12.5%) employed a three-dimensional scanning system to objectively evaluate fat graft survival.ConclusionAutologous fat grafting effectively addresses temporal hollowness, with high patient satisfaction and a favorable safety profile. However, the variability in fat retention rates highlights the need for more controlled studies to establish reliable, validated methods for evaluating fat graft survival in the temporal area, and to further assess the safety of this procedure.